Oracle Cloud Infrastructure Architect Associate All-in-One Exam Guide (Exam 1Z0-1072) - Ramklass, Roopesh (McGraw-Hill, 2020)
Publisher's Note: Products purchased from Third Party sellers are not guaranteed by the publisher for quality, authenticity, or access to any online entitlements included with the product. This study guide covers 100% of the objectives for the Oracle Cloud Infrastructure Architect Associate exam Pass the new Oracle Cloud Infrastructure Architect Associate exam with ease using the detailed information contained in this effective self-study system. Written by an Oracle expert and respected author, Oracle Cloud Infrastructure Architect Associate All-in-One Exam Guide (Exam 1Z0-1072) offers complete coverage of every subject on the challenging exam. Hands-on exercises, practice exam questions with in-depth explanations, "Notes," "Exam Tips," and "Cautions" throughout provide professional insight and call out potentially harmful situations. Beyond exam preparation, this guide also serves as a valuable on-the-job reference. Covers all exam topics, including: " Oracle Cloud Infrastructure concepts " OCI identity and access management " OCI networking " Compute instances " Storage " Database " Automation tools " OCI best practice architectures Online content includes: " 140 practice questions " Fully-customizable online test engine